FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA SUB SEKTOR MAKANAN DAN MINUMAN DI BEI - Tanwijaya, Marcella Bella; Hendra, Hendra (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this research is to examine the factors that influence dividend policy. The independent variables in this study consist of return on assets, current ratio, debt to equity, company size, total asset turnover, and asset growth. The data for this research are food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2020 period. This study used 10 companies and 70 samples and the sample selection procedure used was purposive sampling. The data analysis technique uses descriptive analysis and multiple panel regression. Return on assets and firm size has a positive effect on dividend policy. Its because the return can used by company to share the dividend to shareholders and bigger the company means more assets that could converted into cash. Debt to equity has a negative effect on dividend policy because the company have to pay their obligation, so the company cannot pay the dividend. Meanwhile the other variables have no effect.